Long-term sickness absence trajectories and associated occupational and lifestyle-related factors: a longitudinal study among young and early midlife Finnish employees with pain - Karen Walker-Bone; Tea Lallukka; Ossi Rahkonen; Rahman Shiri; Pi Fagerlund (BMJ Open)
Objectives This study aimed to identify distinct trajectories of long-term sickness absence (LTSA, >10 consecutive working days) among young and early midlife Finnish employees who experienced pain at baseline. It also aimed to determine the pain characteristics and occupational and lifestyle factors associated with these LTSA patterns.Design Longitudinal occupational cohort study with register linkage.Setting The largest municipal employer in Finland.Participants The study population comprised 19–39-year-old Finnish municipal employees (n=1685) who reported pain in 2017.Outcome measures Prospective register data on all-cause LTSA through March 2020 were obtained from the Social Insurance Institution of Finland. Group-based trajectory modelling was used to identify distinct all-cause LTSA trajectories. Multinomial logistic regression was used to examine associations of pain characteristics and work- and lifestyle-related factors with trajectory group membership.Results Three distinct LTSA-trajectory groups were identified: no LTSA (74%), decreasing (18%) and increasing (8%). The decreasing trajectory group had a higher prevalence of chronic or multisite pain, smoking (average marginal effects (AME) 6% points, 95% CI 2 to 11), obesity (AME 8% points, 95% CI 2 to 13), manual or routine non-manual occupation (AME 9% points, 95% CI 4 to 13) and high physical workload, after adjusting for age and gender. No predictor was identified for the increasing trajectory.Conclusion A majority of young and early midlife employees with pain had no LTSA during follow-up; however, chronic and multisite pain, smoking, overweight or obesity, lower occupational class and higher physical workload were associated with the decreasing LTSA trajectory. Interventions at workplaces and in occupational healthcare to prevent LTSA should aim at supporting employees who work with pain and have these risk factors.